Effect of Cu doping on optical and structural properties of ZnO thin films elaborated via sprayed moving nozzle - M. Touati Tliba; B. Benhaoua; A. Benhaoua; A. Rahal; A. H. Hamzaoui (Universty of El-oued جامعة الوادي, 2019)
In this work, 0-5wt.% copper doped zinc oxide thin films were deposited by spray pyrolysis technique (homemade) on 375°C heated glass. Zinc acetate (Zn (CH3COO)2, 2H2O) and copper chloride (CuCl2,7H2O) were used as sources precursor of ZnO and Cu doping, respectively. Effect of copper 0-5wt.% doping concentration on optical and structural properties was studied. UV visible transmission techniques, X-ray diffraction were used respectively to characterize optical and structural properties of elaborated thin films. The average transmittance of all samples was more than 81% in the visible region and become more transparent with Cu doping. Optical gap energy was found to be in 3.25-3.28eV range. X-ray diffraction studies show nanocrystalline thin films with a hexagonal wurtzite structure exhibiting a strong (002) preferred orientation. Particles size ranges in 23- 29nm for 0-5wt.% Cu doped ZnO thin films
Intervention
Keywords: Thin films; Cu doped ZnO; Spray pyrolysis; X-ray diffraction.